An integrated approach to the assessment of work-related stress risk: Comparison of findings from two tools in an Italian methodology. (December 2015) - Ronchetti, M.; Di Tecco, C.; Russo, S.; Castaldi, T.; Vitali, S.; Autieri, S.; Valenti, A.; Persechino, B.; Iavicoli, S.
Highlights: The study describes a mixed methodology to assess work-related stress. Findings showed a good coherence between the results of the two assessment phases. Discrepancies between results of the tools were identified in 16% of the sample. An integrated approach is key to identifying work-related stress risk. Abstract: Introduction: In the past few years much progress has been made in European Union in recognizing the importance of the work-related stress risk, and in adopting specific measures to assess such type of risk. In Italy, the legislative framework on occupational health and safety confirmed the obligation to assess the risk for work-related stress, according to the European Framework Agreement. Material and methods: The Italian Workers' Compensation Authority developed a methodology for the assessment of work related-stress risk as an integrated management risk approach comprising two main assessment tools: a checklist for measuring objective and observational risk indicators and a validated questionnaire to collect employees' perceptions. This study aimed to explore the convergence degree among the results of the two assessment tools in a sample of 137 companies. Results: By applying the univariate ANOVA the mean values of the questionnaire were compared to the levels of risk obtained in the preliminary assessment. The analyses highlighted that when the risk is higher in the preliminary assessment, there is an increase in the perceptions of the risk factors. In line with Cohen's methodological guidelines findings revealed moderate values. Finally, the analysis of discrepancies shows a good concordance level among the results of the two assessment phases. Conclusions: The study highlighted the effectiveness and reliability of the INAIL's methodology. Such process enables companies to use two complementary tools for a more complete definition of the risk factors, in order to develop interventions.